Investigation on efficiency of in-wheel BLDC motors for different winding structures - SAĞLAM, ŞAFAK (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
Electric machine windings are the essential elements which affect machine performance and efficiency substantially. Two main criteria are considered during winding design: impact on performance and manufacturing costs. In this study, different winding structure combinations are investigated by implementing in an in-wheel motor structure. The motor is a surface mounted permanent magnet BLDC motor which is intended to use in light electric vehicles. According to the design data, the obtained optimum design is manufactured and tested. Accurately captured test results are compared to the calculated values. The direct drive in-wheel BLDC motor used in this study has the rated values of 2.5 kW output power, 900 min-1 shaft speed and 150 V terminal voltage. A Finite Element Method (FEM) based software is used for the design study, that is called ANSYS Electronics Desktop. Effects of different winding topologies are studied by keeping the motor structure and materials unchanged. The validation of the optimized design is realized by conducting the performance experiments. The study shows that the winding topology has a great importance especially for in-wheel motors.
Keywords: In-Wheel BLDC motor; efficiency; winding shape; light electric vehicle